The Impact of the New Complex of Threats on Human and Societal Resilience in The Baltic Sea Region Countries During Periods of Shocks - Rakauskiene, Ona Grazina; Androniceanu, Armenia; Visokaviciene, Birute; Volodzkiene, Lina (Transformations In Business & Economics, 2026)
The contemporary world is increasingly shaped by multiple overlapping threats, including pandemics, socio-economic inequality, geopolitical tensions, climate change, and technological risks. These challenges create new forms of uncertainty that affect both individuals and societies. In this context, strengthening human and societal resilience has become an important condition for sustainable development. This paper examines the impact of this new complex of threats on human and societal resilience in the Baltic Sea Region (BSR) countries during periods of shocks. The aim of the study is to assess how major global threats influence human development and resilience in the BSR countries and to identify possible directions for strengthening resilience. The analysis focuses on ten countries of the region: Denmark, Sweden, Finland, Germany, Estonia, Latvia, Lithuania, Poland, Norway, and Iceland. The research relies on the analytical framework of the United Nations Development Programme and uses indicators such as the Human Development Index (HDI), the Inequality-adjusted Human Development Index (IHDI), and the Planetary Pressures-adjusted Human Development Index (PHDI). The results show that although human development in the BSR countries has generally improved, significant differences remain between country groups. Inequality and planetary pressures reduce the potential of human development and weaken resilience, while countries with higher development levels demonstrate greater capacity to withstand shocks. The findings highlight the importance of reducing inequality, strengthening human potential, and integrating social, economic, and environmental policies in order to build more resilient societies in the Baltic Sea Region.